Collecting self-report research data with people with dementia within care home clinical trials: Benefits, challenges and best practice. (January 2021) - Perfect, Devon; Griffiths, Alys W; Vasconcelos Da Silva, Miguel; Lemos Dekker, Natashe; McDermid, Joanne; Surr, Claire A
One-third of people with dementia live in care home settings and in order to deliver better evidence-based care, robust research including clinical trials is required. Concerns have been raised by researchers about the capacity of care home residents with dementia to participate in clinical trials. This includes self-report measures, completion of which researchers have suggested may be unreliable or impossible and may cause distress for residents. Many trials, therefore, utilise only proxy completed outcome measures. This is despite evidence that individuals with mild through to advanced dementia can reliably report on outcomes, if appropriate measures and approaches to data collection are used. However, little has been written about best practice in data collection with this group. This study aimed to explore the experiences of researchers working on dementia trials in care homes and identify best practices to assist design of future trials. Thirty-three researchers completed an online, qualitative questionnaire outlining their experiences and the perceived benefits and challenges of data collection with people with dementia. We identified five main benefits: (1) improving the delivery of person-centred care, (2) hearing the voice of people with dementia, (3) residents spending time with researchers, (4) improving researcher understanding, and (5) having an evidence base from multiple sources. We also identified five main challenges: (1) effective communication, (2) fluctuating capacity, (3) causing distress to residents, (4) time pressures, and (5) staff availability. Researchers also made suggestions about how these can be overcome. We recommend that the challenges identified could be overcome using appropriate methods for collecting data. Thorough training for researchers on data collection with people with dementia was identified as important for ensuring successful data collection.